Politeness Judgment from Responding to Blame Utterances in Thai:: Perspectives from Two Generations - ไทยแท้ ศิรวัตร (Journal of Letters, 2019)
To determine whether any action or utterance is polite or impolite is at the discretion of the listener; a speaker may employ utterances that seem disrespectful to an outside audience, but if their immediate listeners did not feel those utterances were impolite, the utterances cannot be regarded as such. However, personal politeness perspectives vary according to the participants’ age range. For this reason, an awareness of the participants’ view of politeness is important. If people from different generations realize each other’s politeness perspectives, it makes their communication smooth. This article aims to comparatively study the politeness judgment levels of utterances taken from dialogue in TV series in situations where teenagers responded to blame from their parents. The data were collected from two groups of participants: 30 teenagers and 30 adults. The results show that there are differences between the politeness judgements of teenagers and adults, which are reflected in the reasoning behind the judgments. It was found that adults focused on negative behavioral reasons such as emotional expression, controversy, and aggressive expression, while teenagers emphasized giving explanations.